2010
DOI: 10.1177/0305829810372781
|View full text |Cite
|
Sign up to set email alerts
|

Why They Don’t Hate Us: Emotion, Agency and the Politics of ‘Anti-Americanism’

Abstract: This article reconceptualises the emotions associated with 'anti-Americanism' and sketches an alternative account of impassioned protest in the Middle East and South Asia. I identify two overlapping discursive images that mistake what emotions are and how they fuel political resistance: 'Islamic anger', which delegitimises emotional expression as a form of political agency, and 'anti-American hatred', which assumes that popular emotions in these regions are tied to a clear and distinct object -America. Drawing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Representations of mass emotion can serve to delegitimize the political claims and agency of certain actors, as indicated by the long history of efforts to describe revolutionary movements and crowds as emotionally driven disruptions to social stability (Ginneken, ; Van Rythoven, ). In some cases, mass emotions may be regarded as authentic emotional expressions of some culturally divergent community—as in the essentializing notion of “Islamic rage” (Ross, ). Here, mass emotions are attributed to communities on the opposite side of a politically salient marker of difference, whether national, religious, class‐based, gender, or racial, in ways that further work to generate dangerous, irrational, or untrustworthy others (Bilgic, Hoogensen Gjørv, & Wilcock, ).…”
Section: Emotion Affect Collective Experience and Identitymentioning
confidence: 99%
“…Representations of mass emotion can serve to delegitimize the political claims and agency of certain actors, as indicated by the long history of efforts to describe revolutionary movements and crowds as emotionally driven disruptions to social stability (Ginneken, ; Van Rythoven, ). In some cases, mass emotions may be regarded as authentic emotional expressions of some culturally divergent community—as in the essentializing notion of “Islamic rage” (Ross, ). Here, mass emotions are attributed to communities on the opposite side of a politically salient marker of difference, whether national, religious, class‐based, gender, or racial, in ways that further work to generate dangerous, irrational, or untrustworthy others (Bilgic, Hoogensen Gjørv, & Wilcock, ).…”
Section: Emotion Affect Collective Experience and Identitymentioning
confidence: 99%
“…The progression in hostility toward the US increased the chances of supporting terror and extremism in Muslim countries (Van Ginneken, 2007). According to Ross (2010), anti-US sentiments worldwide are significantly causative to the US recession. According to Berger (2014), a study conducted by Pew Foundation in Muslim majority countries indicated that the majority of the people in those countries were intended to refuse US products and services.…”
Section: Introductionmentioning
confidence: 99%
“…2 Sterling-Folker rightly argues that realists need to reclaim their controversial concern for human biology but with attention to the variability of its effects in the social world (2002,. I argue that elements of this orientation already exist in the work of Morgenthau and Niebuhr. theory -in order to make sense of what emotions are and how they affect political behavior (Ross 2006(Ross , 2014Bially Mattern, 2011;Bleiker and Hutchison 2008;Crawford 2009;Mercer 2010;Hall 2011;Sasley 2011). In the meantime, under our noses lies a theoretical tradition -political realism -whose long-standing concern for evil, fear, and tragedy indicates a potentially bountiful source for thinking about human emotion and its role in international politics.…”
mentioning
confidence: 99%
“…7 Recent work in cultural theory builds on the account of French social theorist Gilles Deleuze. See, for example,Connolly (2002),Ross (2006), and the essays inGregg (2010). 280 A N D R E W A . G .…”
mentioning
confidence: 99%
See 1 more Smart Citation